Asian–Pacific Oscillation signal from a Qomolangma (Mount Everest) ice-core chemical record. Issue 66 (2014) - Xu, Hao; Hou, Shugui; Pang, Hongxi
Abstract: The Asian–Pacific Oscillation (APO) is a climate pattern related to the thermal differences between the Asian continent and the north Pacific. We present a 1000 year record of the major ions in a 108.83 m ice core from east Rongbuk glacier (28°01′ N, 86°58′ E; 6518ma.s.l.) on the northeast slope of Qomolangma (Mount Everest), and discuss its relationship with a 993 year time series of the summer APO index that has been reconstructed from Beijing's summer temperature (recorded by a stalagmite) and the Pacific Decadal Oscillation (PDO) index. Empirical orthogonal function (EOF) analysis shows that crustal major ions (Mg 2+, Ca 2+, SO4 2– and NO3 – ) are highly loaded on EOF1, whereas marine major ions (Cl – and Na + ) are highly loaded on EOF2. Higher EOF1 is associated with lower upper-troposphere temperature (UTT) over Mongolia, corresponding to a lower APO index and higher surface pressure. Higher EOF2 is associated with higher UTT over Mongolia, corresponding to a higher APO index and lower surface pressure. The higher burden of major ions and higher summer APO index during the period AD 1000–1323 may be due to drought and warm climate of the major-ion source regions. From AD1323 to 1900, EOF1 and EOF2 do not show a consistent correlation with summer APO index, indicating the complex mechanisms of ion transport over the southern Tibetan Plateau (TP) during this period. After AD 1900, the summer APO index is correlated negatively with EOF1 and positively with EOF2, indicating that ion transport over the southern TP during this period is influenced significantly by the APO. Our examinations of the PDO index and major-ion record show that higher PDO corresponds to higher EOF1 and lower EOF2. This suggests that the correlation between the recorded major-ion concentration and the APO index originates in the seesaw relationship in temperature between the Asian continent and the north Pacific.